TERT Promoter Mutations and Telomerase in Melanoma. (19th July 2022) - Guo, Yuchen; Chen, Yi; Zhang, Lianghui; Ma, Ling; Jiang, Keyu; Yao, Gang; Zhu, Lingjun
Abstract : Malignant melanoma is an extremely malignant tumor with a high mortality rate and an increasing incidence with a high mutation load. The frequency of mutations in the TERT promoter exceeds the frequency of any known noncoding mutations in melanoma. A growing number of recent studies suggest that the most common mutations in the TERT promoter (ATG start site −124C>T and −146C>T) are associated with increased TERT mRNA expression, telomerase activity, telomere length, and poor prognosis. Recently, it has been shown that TERT promoter mutations are more correlated with the occurrence, development, invasion, and metastasis of melanoma, as well as emerging approaches such as the therapeutic potential of chemical inhibition of TERT promoter mutations, direct telomerase inhibitors, combined targeted therapy, and immunotherapies. In this review, we describe the latest advances in the role of TERT promoter mutations and telomerase in promoting the occurrence, development, and poor prognosis of melanoma and discuss the clinical significance of the TERT promoter and telomerase in the treatment of melanoma.